Laser Lithotripsy — The New Wave - J Hochberger; C Ell (Canadian Journal of Gastroenterology)
Currently more than 90% of all common bile duct concrements can he removed via the endoscopic retrograde route by means of endoscopic papillotomy, stone extraction by baskets and balloon catheters, or mechanical lithotripsy. Oversized, very hard or impacted stones however often st ill resist conventional endoscopic therapy. Laser lithotripsy represents a promising new endoscopic approach to the nonsurgical treatment of those common bile duct stones. Currently only short-pulsed laser systems with high power peaks but low potential for thermal tissue damage are used for stone fragmentation. Systems in clinical applications are the pulsed free-running-mode neodymium YAG (Nd:YAG) laser (1064 nm, 2 ms) and the dye laser (504 nm, 1 to 1.5 μs). Energy transmission via highly flexible 200 ìm quartz fibres allows an endoscopic retrograde approach to the stone via conventional duodenoscope or mother-baby-scope systems. New systems currently in preclinical and first clinical testing are the Q-switched Nd:YAG laser (1064 nm, 20 ns) and the Alexandrite laser (700 to 815 nm, 30 to 500 ns). By means of extremely short nanosecond pulses (10-9 s) for the induction of local shock waves at the stone surface, possible tissue damage is even more reduced. No complications have been reported so far after applying laser lithotripsy clinically in about 120 patients worldwide. Compared to extracorporeal shock wave treatment, laser lithotripsy can be executed in any endoscopy unit in the scope of the endoscopic pretreatment and does not require general anesthesia, which is often necessary for extracorporeal shock wave lithotripsy.